Response of strawberry plants inoculated with Azospirillum and Burkholderia at field conditions = Respuesta de plantas de frutilla inoculadas con Azospirillum y Burkholderia en condiciones de campo - Lovaisa, Nadia Carolina; Guerrero Molina, María Fernanda; Delaporte Quintana, Paola Adriana Georgina; Salazar, Sergio Miguel (Facultad de Agronomía y Zootecnia, Universidad Nacional de Tucumán, 2019)
The use of synthetic fertilizers is a most common practice used to incorporate nutrients in agricultural soils; these are expensive leading to increases in the total crop-production costs. This traditional crop management may turn inefficient and polluting as part of the nutrients can be lost by lixiviation or become insoluble by cation exchange. Therefore, the aim of this study was to evaluate the agronomic response of strawberry plants (Fragaria ananassa Duch.) inoculated with two native PGPB as a biotechnological alternative to the plant nutrition. The experiment was carried out under field conditions during 2014, using strawberry plants cv. ‘Fortuna Florida’ inoculated with the local strains Azospirillum brasilense REC3 and Burkholderia vietnamensis AFTV3, applied individually and combined. Results showed greater growth index (30%) and relative chlorophyll content in leaves (10%) in inoculated plants compared to non-inoculated controls, and also increased commercial fruit yield in plants inoculated with A. brasilense REC3 (12.6%), B. vietnamensis AFTV3 (13.4%) and both (7.2%) in comparison with uninoculated controls.